2013
DOI: 10.1136/annrheumdis-2013-203794
|View full text |Cite
|
Sign up to set email alerts
|

HRES-1/Rab4-mediated depletion of Drp1 impairs mitochondrial homeostasis and represents a target for treatment in SLE

Abstract: Objective Accumulation of mitochondria underlies T-cell dysfunction in systemic lupus erythematosus (SLE). Mitochondrial turnover involves endosomal traffic regulated by HRES-1/Rab4, a small GTPase that is overexpressed in lupus T cells. Therefore, we investigated whether (1) HRES-1/Rab4 impacts mitochondrial homeostasis and (2) Rab geranylgeranyl transferase inhibitor 3-PEHPC blocks mitochondrial accumulation in T cells, autoimmunity and disease development in lupus-prone mice. Methods Mitochondria were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
134
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 43 publications
13
134
1
1
Order By: Relevance
“…These findings are consistent with earlier observations that mitochondrial dysfunction of T cells is confined to patients with SLE relative to other rheumatic diseases (14,15,20). Here, we also confirm that NO is overproduced in patients with SLE (20), which is consistent with a role of NO in mitochondrial biogenesis (19,21,22) and increased mitochondrial mass in lupus T cells (4,11,20). NO production is also increased in lupus-prone mice, underlying its importance for lupus pathogenesis (23,31).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with earlier observations that mitochondrial dysfunction of T cells is confined to patients with SLE relative to other rheumatic diseases (14,15,20). Here, we also confirm that NO is overproduced in patients with SLE (20), which is consistent with a role of NO in mitochondrial biogenesis (19,21,22) and increased mitochondrial mass in lupus T cells (4,11,20). NO production is also increased in lupus-prone mice, underlying its importance for lupus pathogenesis (23,31).…”
Section: Discussionsupporting
confidence: 92%
“…In turn, sustained exposure to NO triggers mitochondrial biogenesis (20,21). Thus, oxidative stress in SLE is associated with the accumulation of mitochondria that may be driven by increased NO-initiated biogenesis (20) and diminished mitophagy (4). While mitochondria are traditionally considered a primary source of energy production through oxidative phosphorylation, recent studies have clearly shown that they also regulate many signaling pathways, including T-cell activation and death pathway selection (10).…”
mentioning
confidence: 99%
“…[16][17][18] This deregulation could contribute to autoreactive T-cell survival and can be put in line with the deregulation of both macroautophagy and chaperone-mediated autophagy (CMA) in B cells that has been recently described to occur in lupus. 19,20 To date, however, these data remain correlative and no study has been published describing an in vivo model, prone to systemic autoimmunity, with specific autophagy deletion in B cells.…”
mentioning
confidence: 91%
“…The authors did not evaluate the effects of TCR-related stimulation, which would have been particularly relevant on naïve T cells isolated from SLE patients. Two other studies also recently showed an increase of autophagic activity first, in peripheral blood lymphocytes from SLE patients and second, in CD4 T cells (Caza et al, 2014;Clarke et al, 2014). Thus, the question still remains open -is macroautophagy activity globally increased or decreased in lupus T cells?…”
mentioning
confidence: 97%